Developing extended ISA on RISC based processor - Lee, Ang (2023)
In this model era, the digital market is grown rapidly and great quantities of product required processor for their applications. Therefore, the demand of processor is continuously increased, especially RISC-V processors which are durable and adaptable in its instruction set architectures. RISC-V processors are gaining traction in a variety of applications and research fields. This work aims to develop extended ISA on RISC-V based processor. Those ISA can help the application to accelerate progress during execution and improve the performance. Therefore, it is a useful product since it preserves software compatibility while also allowing for differentiation and innovation. This project will show how it develops a RISC-V RV32I processor and its extension by logic gates and simulates by using Verilog code in ModelSim.